ANALISIS KUALITAS AIR SUNGAI POOPOH KECAMATAN TOMBARIRI KABUPATEN MINAHASA - Martino Elvis Presley Sukiman; Maxi Tendean; Sri Sulastriningsih (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2021)
The problem in this study is the existence of community activities that dispose of household waste and toilet waste directly into the Poopoh River. This study aims to analyze and obtain river water quality data. This type of research is a quantitative research using a fixed sample water sampling method. The parameters measured were pH, DO (Dissolved Oxygen), BOD (Biological Oxygen Demand), and TSS (Total Suspended Solid). The results showed that there had been a decrease in the quality of river water in the downstream part of the river as seen from the results of laboratory tests which stated that the pH level in the upstream part of the river reached 6.94 and downstream increased to 7.98. The level of BOD in the upper reaches of the river is 1.8 and in the lower reaches of the river rises to 26.95. The DO level in the upstream part of the river is 7.5 and at the downstream level, it drops to 1.62. The TSS level in the upper reaches of the river is 5 and in the lower reaches of the river, it has increased to 20. It can be seen that there has been a decrease in the quality of river water from upstream to downstream, especially in the parameters of BOD and DO.